(3ZGjI GdbQH aj TQM fgGjI GdWdHs - (3eMjj GdOjf YHO GdbGOQ Hf TjN Hf YHO Gddg GdYjOQhSj,J (B1038 (3g` s ((3QVhGf Hf CMeO Hf YHO GdQMef HGQVhGf HGaVd s)
(3ChdgG (B:s
(3GdMeO ddg GdPi TQY GdbGUOjg CbUQ WQjb (B,(3HYO abO ef Gdgd JYGdi Ydi hdg GdMeO s
(3BNQgG (B:s
(3Yf QGHY LeGOi GdBNQ YGe KeGf hJSYjf hJSYeGFI hGdMeO ddg QH GdYGdejf s
(3Vef eLehY , JQJjHgG (B: (3ef U (B77 - (3U(B83s
(3HgG fXGe GdJYbjHIs
(3bhHdJ GdfSNI Ydi GdCUd Gdefbhd efg MSH GdWGbIs
(3hbQFJ GdfSNI Ydi YHO Gddg Hf Ydi Hf TgGH GdOjf hYdi CMeO Hf eMeO GdMHTi Ydhi SfI (B1236 (3g s
(3`hbO cJHJ CHjGJ GdbUjOI HGdMeQIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
Keywords: (3Gdabg GdTGaYjs